(untitled) (Revista Cientifica Ingenio Magno, 2023)
The necessity to inspect and evaluate large engineering structures, without point-to-point time-consuming inspections, has been a motivation to implement different confident and faster techniques. A growing technique is the use of guided waves. The implementation of guided waves such as Lamb waves, recently has been increasing for nondestructive evaluation in plate-like structures and components. However, Lamb wave multimode and inherent noise can interfere to identify properly Lamb wave mode propagation. In this work, the identification of Lamb wave modes propagated in thin metallic plates using Short Time Fourier Transform (STFT) has been implemented. The identification of Lamb waves was using dispersive curves computed for an aluminum plate with 1.9 mm in thickness. Experimental Lamb waves were generated using piezoelectric sensors and then digitalized to compute STFT in measured signals. Subsequently, theoretical dispersive curves were plotted over spectrograms obtained from analyzed measured signals, to identify the experimentally generated lamb wave modes. Results show that the proposed methodology is feasible for the identification of Lamb wave modes, at three different excitation frequencies to excite Lamb wave modes.